Sentiment and Authority Analysis in Conversational Content - Machová, Kristína; Mikula, Martin; Szabóová, Martina; Mach, Marián (Computing and Informatics, 2018)
This paper deals with mining conversational content from the social media. It focused on two issues: opinion and emotion classification and identification of authoritative reviewers. The paper also describes applications representing the results obtained in the given areas. Authority identification can be used by organizations to search for experts in their specific areas to employ them. The opinion and emotion analysis can be useful for providing decision-making support.